МОНГОЛ ХЭЛНИЙ -Ч ДЭД БҮТЭЭВРИЙН ОНЦЛОГ, НАЙРУУЛГЫН ҮҮРЭГ - М.Энхжаргал (Acta Mongolica, 2014)
Morphemes are the smallest individually meaningful elements in the utterances of a language. Thus the morphemes are all meaningful. There are many methods for forming new words in the contemporary Mongolian language and one of them is word formation by suffixes. New word is formed with connected suffix to its root. However, the exciting phenomenon that new word has no semantic meanings is emerged when suffix connected to word roots. In morphology, it is called sub morph. The present article has reviewed the emerged meaning, structure and classification of those sub morphs in Mongolian language along with examples from the literature. There are many concepts such as sub tune, sub pronunciation, sub meaning and sub part in the linguistics and “Submorph” the object of our study is considered as one of those concepts. It is subunit at the lingual morpheme level and generally this subunit has no particular semantic meaning when it connected to word roots, but minor variance in the applied stylistics. Therefore the subunit of lingual morpheme has the different definition and title for instance E.A Zemskaya, E.C Kubryakova “Sub morph”, N.M Shanskii “Affecksoide”, D. S. Vort “Morpheme no semantic meaning”, V.V Lopatin “redundant” or “insert” morpheme, G. O Vinocur “ variation of root”, A. I Moiseev “quasi-morpheme” etc. Although these titles seem different, they have defined the main characteristics of sub morph. Many sub morphs namely as -га4, -с, -м, -ж, -ч, -р, -аа4,-ц, -н, -т are found in Mongolian language, among them -га4, -с suffixes are mostly used in word formation. As summarized from the preceding reviews and studies from the named scientists, sub morphs emerged in Mongolian language morphology is become the attractive object of the study.